2018
DOI: 10.1177/2329048x18795277
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of the Long-Term Outcome of Drug-Resistant Epilepsy in Children Treated in Urban India

Abstract: Objective:To study the outcome of childhood-onset drug-resistant epilepsy.Methods:Fifty-five patients with drug-resistant epilepsy, meeting inclusion criteria, were identified from the Pediatric Neurology Clinic database with seizure onset less than age 13 years and a minimum follow-up of 5 years. Seizure remission was defined as no more than 1 seizure/year. Kaplan-Meier analysis was used to calculate the annual probability of seizure remission. Chi-square/Kruskal-Wallis tests were used to detect differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Childhood DRE risk is serious and can have catastrophic effects on neurodevelopment. [ 22 , 23 ] The brain undergoes an extended period of growth and maturation during the first 2 years of life. Thus, intractable seizures are refractory during this critical time, particularly in the early infancy, can negatively affect the cognitive and motor development, consider by affecting the children's cognitive, behavioral, and psychiatric function.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood DRE risk is serious and can have catastrophic effects on neurodevelopment. [ 22 , 23 ] The brain undergoes an extended period of growth and maturation during the first 2 years of life. Thus, intractable seizures are refractory during this critical time, particularly in the early infancy, can negatively affect the cognitive and motor development, consider by affecting the children's cognitive, behavioral, and psychiatric function.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic characteristics in drug-resistant epilepsy of published research (2014-2020) The genes shown in bold are common gene mutation amid studiesDiscussionChildhood DRE risk is serious and can have catastrophic effects on neurodevelopment[22,23]. The brain undergoes an extended period of growth and maturation during the rst 2 years of life.…”
mentioning
confidence: 99%